Environmentally friendly high-energy MOFs: crystal structures, thermostability, insensitivity and remarkable detonation performances. Issue 2 (15th December 2014) - Liu, Xiangyu; Gao, Wenjuan; Sun, Panpan; Su, Zhiyong; Chen, Sanping; Wei, Qing; Xie, Gang; Gao, Shengli
Abstract : Three environmentally friendly MOF-based HEDMs with high-nitrogen ligands present superior detonation properties, thermostability and insensitivity. Abstract : An alternative method to prepare new-generation green high-energy-density materials with excellent performances has been developed on the basis of a coordination chemistry strategy. In the present work, hydrothermal reaction of Cu(ii )/Cu(i ) with a rigid nitrogen-rich ligand, 3-(1 H -tetrazol-5-yl)-1 H -triazole (H2 tztr), led to three high-energy metal–organic frameworks (MOFs): [Cu(Htztr)2 (H2 O)2 ] n (1 ), [Cu(tztr)]·H2 O n (2 ) and [Cu(Htztr)] n (3 ). Referring to the coordination geometry configuration of Cu(ii )/Cu(i ) and flexible coordination fashion of the ligand, the energies of the complexes1–3 are gradually improved when they are structurally transformed from1, a mononuclear structure to2, a 3D porous MOF incorporated with guest water molecules to3, a well-isolated layer structure. The title complexes show outstanding thermostability ( T dec = 345 °C for1, 325 °C for2 and 355 °C for3 ) and low sensitivity, confirmed by experimental and theoretical characterization. Notably, complex3 features superior detonation properties to that of known energetic MOFs.